Limits to market power: Strategic discourse and institutional path dependence in the European Union–African, Caribbean and Pacific Economic Partnership Agreements. (June 2017) - Heron, Tony; Murray-Evans, Peg
The following article offers a critical engagement with recent economic constructivist scholarship as a means of understanding the nature of the European Union's 'market power'. It does so by focusing on the African, Caribbean and Pacific group of countries, and seeks to explain why — in spite of the European Union's preponderant market power — the goal of promoting trade liberalisation and regulatory harmonisation through regional Economic Partnership Agreements (EPAs) ultimately fell short of original ambitions. We highlight the inadequacies of materialist accounts of the European Union's market power in this case and instead take our cue from the (predominantly) constructivist literature emphasising the role of transnational advocacy coalitions. We argue, however, that the latter do not go far enough in their exploration of the non-material correlates of the European Union's market power by considering fully its discursive dimension. To address this shortcoming, we draw on Craig Parsons' distinction between ideational and institutional logics of explanation to understand how the invocation of institutional constraints affects the impact of particular discursive strategies. We argue that, in our specific case, the success or failure of the Economic Partnership Agreements rested not just on the fungibility (or otherwise) of the European Union's material power or the campaigning of transnational coalitions, but on the congruence between the ideas used by European Union policy actors to justify the Economic Partnership Agreements and the institutional norms associated with the setting in which these ideas were deployed.